Designing nanoscale constructs from atomic thin sheets of graphene, boron nitride and gold nanoparticles for advanced material applications. - Jasuja, Kabeer (Kansas State University, 2011)
Nanoscale materials invite immense interest from diverse scientific disciplines as these provide access to precisely understand the physical world at their most fundamental atomic level. In concert with this aim of enhancing our understanding of the fundamental behavior at nanoscale, this dissertation presents research on three nanomaterials: Gold nanoparticles (GNPs), Graphene and ultra-thin Boron Nitride sheets (UTBNSs). The three-fold goals which drive this research are: incorporating mobility in nanoparticle based single-electron junction constructs, developing effective strategies to functionalize graphene with nano-forms of metal, and exfoliating ultrathin sheets of Boron Nitride. Gold nanoparticle based electronic constructs can achieve a new degree of operational freedom if nanoscale mobility is incorporated in their design. We achieved such a nano-electromechanical construct by incorporating elastic polymer molecules between GNPs to form 2-dimensional (2-D) molecular junctions which show a nanoscale reversible motion on applying macro scale forces. This GNP-polymer assembly works like a molecular spring opening avenues to maneuver nano components and store energy at nano-scale. Graphene is the first isolated nanomaterial that displays single-atom thickness. It exhibits quantum confinement that enables it to possess a unique combination of fascinating electronic, optical, and mechanical properties. Modifying the surface of graphene is extremely significant to enable its incorporation into applications of interest. We demonstrated the ability of chemically modified graphene sheets to act as GNP stabilizing templates in solution, and utilized this to process GNP composites of graphene. We discovered that GNPs synthesized by chemical or microwave reduction stabilize on graphene-oxide sheets to form snow-flake morphologies and bare-surfaces respectively. These hybrid nano constructs were extensively studied to understand the effect and nature of GNPs’ interaction with graphene, and applied to address the challenge of dispersing bare-surfaced GNPs for efficient liquid-phase catalysis. We also revisited the functionalization of graphene and present a non-invasive surface introduction of interfaceable moieties. Isostructural to graphene, ultrathin BN sheet is another atomic-thick nanomaterial possessing a highly diverse set of properties inconceivable from graphene. Exfoliating UTBNSs has been challenging due to their exceptional intersheet-bonding and chemical-inertness. To develop applications of BN monolayers and evolve research, a facile lab-scale approach was desired that can produce processable dispersions of BN monolayers. We demonstrated a novel chlorosulfonic acid based treatment that resulted in protonation assisted layer-by-layer exfoliation of BN monolayers with highest reported yields till date. Further, the BN monolayers exhibited extensively protonated N centers, which are utilized for chemically interfacing GNPs, demonstrating their ability to act as excellent nano-templates. The scientific details obtained from the research shown here will significantly support current research activities and greatly impact their future applications. Our research findings have been published in ACS Nano, Small, Journal of Physical Chemistry Letters, MRS Proceedings and have gathered >45 citations.
Keywords: Nanotechnology; Graphene; Boron nitride; Gold nanoparticles; Chemical Engineering (0542)